Relationship between Stress Level of USU Faculty of Medicine Students and Primary Headache during Online Lectures - Afra Meutia Nasution; Haflin Soraya Hutagalung (Talenta Publisher, 2023)
Background: COVID-19 has made lectures turn online. This sudden change can cause stress for students. Stress levels in students are ranging from mild, moderate, to severe stress. There are few symptoms of stress experienced by these students and headache is one of the common forms of stress.Objective: This study aims to determine the association between the stress level of USU Medical Faculty students with primary headaches during online lectures. Methods: The study used observational analytical methods by design cross-sectional study. The sample was 262 students of the Faculty of Medicine, Universitas Sumatera Utara who met the inclusion criteria. The data used is primary data that will be obtained from questionnaires filled out online through the application Line, WhatsApp and Instagram. Results: Of the 77 respondents, 48 were female (62.3%), and 29 were male (37.7%). There are 42 students who experience primary headaches, and 27 suffer from moderate stress, 9 mild stress and 6 severe stress. In the chi-square test, there is a significant association between stress levels and primary headaches with a value of p=0.010 (p<0.05). Conclusion: There is an association between the stress level of USU Medical Faculty students and primary headaches during online lectures.